Mitochondria: Master Regulator of Metabolism, Homeostasis, Stress, Aging and Epigenetics - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Mitochondria became a driving force in evolution due to their ability to manufacture adenosine triphosphate (ATP) through respiration. The functioning of mitochondria within eukaryotic cells has evolved dramatically as a result of evolution. Recent research has revealed mitochondria form plasticity to keep the cell's needs and function.CONTENT: Mitochondria have long been regarded as the cell's